2010
DOI: 10.17656/jzs.10217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Condition Score on Productive Performance of Local Karadi Cows

Abstract: Twenty one Karadi cows raised at Bakrajo Farm, College of Agriculture, University of Sulaimani, Kurdistan Region, Iraq, over the period April 2006 – May 2007 were used in this study. Cows were naturally mated, then calved between 13th of June 2006 and 21st of January 2007. Cows were scored according to the East of Scotland College of Agriculture system (ESCA) for their body condition at two periods; sixty days before the expected calving, and at calving (1-3 days after calving). Data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…During early lactation, BCS had positive association with milk production, negative with milk protein and no association with milk fat in Peranakan Etawah goats between BCS 2 to 4 as suggested by Susilorini et al (2014). Few other studies also showed that BCS has high correlation with milk production and composition (Zahraddeen et al 2009, Ahmed et al 2010and Pambu et al 2011) as well as it affects the reproduction performance of dairy animals (Suharto et al 2008 andSerin et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…During early lactation, BCS had positive association with milk production, negative with milk protein and no association with milk fat in Peranakan Etawah goats between BCS 2 to 4 as suggested by Susilorini et al (2014). Few other studies also showed that BCS has high correlation with milk production and composition (Zahraddeen et al 2009, Ahmed et al 2010and Pambu et al 2011) as well as it affects the reproduction performance of dairy animals (Suharto et al 2008 andSerin et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Influence of pre partum body condition score on milk production [22] . The results of [23] exhibited that the body condition score at drying (BCSD) and at calving (BCSC) significantly affected milk production during the first 8 weeks, total milk production, peak production and persistence, as the body condition categories (3, 3.25, 3.5) outperformed during the dry period, and (3, 3.5) at parturition on the rest of the body condition categories in total milk production, and skinny cows with body condition score (2, 2.25, 2.5) gave a lower peak of production compared to the rest of the body condition categories. This explains that cattle with a high body condition score suffer from a high negative energy balance value, which is due to the high body stock, and a low body condition score suffers from a decrease in body reserves during the prenatal period, which controls their production, especially at the beginning of the lactation season or during the early stage of lactation period [22].…”
Section: Bcs Highmentioning
confidence: 99%